The association between blood sugar control and hearing impairment in individuals with type 2 diabetes mellitus: a prospective study using otoacoustic emissions as a biomarker - Walia, Inderpal Singh; Kumar, Sanjay; Singh, Shailendra; Biradar, Kashiroygoud; Kumar, Sudheer (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The existing association between hearing impairment and diabetes mellitus (DM) prompted us to investigate the relationship between glycaemic control, as measured by HbA1c levels, and hearing impairment in individuals with type 2 diabetes mellitus (T2DM). Methods: In this study, we assessed the auditory function of a sample of 100 individuals diagnosed with T2DM, who were aged 30 years or older and had a disease duration of at least 5 years. The evaluation was conducted using distortion product otoacoustic emissions and transient evoked otoacoustic emissions. The criteria for poor glycaemic control were established as HbA1c levels equal to or exceeding 7.5%. Results: Individuals with a haemoglobin A1c (HbA1c) level of 7.5% or higher exhibited a nearly threefold increased likelihood of developing hearing impairment in comparison to those with lower HbA1c levels. The gender-based observation revealed a stronger association in females, although the observed correlation did not reach statistical significance. Conclusions: The findings of our study establish a significant association between inadequate management of blood glucose levels and the occurrence of hearing impairment among individuals with T2DM. These results underscore the importance of achieving optimal glycaemic control as a means of preventing hearing impairment in this patient population. Further investigation is required to substantiate these findings through a comprehensive and longitudinal research approach.